Do decision makers have subjective probabilities? An experimental test - David Ronayne; Roberto Veneziani; William R. Zame (Queen Mary University of London, School of Economics and Finance, 2022)
Anscombe and Aumann (1963) offer a definition of subjective probability in terms of comparisons with objective probabilities. That definition - which has provided the basis for much of the succeeding work on subjective probability - presumes that the subjective probability of an event is independent of the prize consequences of that event, a property we term Prize Independence. We design experiments to test Prize Independence and find that a large fraction of our subjects violate it; thus, they do not have subjective probabilities. These findings raise questions about the empirical relevance of much of the literature on subjective probability.
Keywords: D01; D81; D84; C09; 330; subjective probability; choice under uncertainty; online experiments